SINTESIS PEREKAT TANIN RESORSINOL FORMALDEHIDA DARI EKSTRAK KULIT POHON MANGIUM UNTUK PENINGKATAN KUALITAS BATANG SAWIT - Okti Rachmawati; Purwantiningsih Sugita; Adi Santoso (Jurnal Penelitian Hasil Hutan, 2018)
Oil palm trunk is lower in dimensional stability, density, physical, and mechanical properties than other wood species. Efforts to overcome the weakness of the oil palm trunk properties could be conducted through densification with hot pressing and chemical adhesive addition. This paper studies optimum composition of Tannin Resorcinol Formaldehyde (TRF) in its application for improving the quality of oil palm trunk. The tannins were water extracted at 75°C and further copolymerized with resorcinol and formaldehyde. TRF was studied through functional group analysis using infrared spectroscopy and cristallinity test using X-ray diffraction. The TRF adhesive was applied through compregnation process. Results showed that reactivity of tannins in bark of Acacia mangium was 65.82%, the optimum adhesive composition of TRF (v/v) was = 1:0.05:0.05 with solid content of 8.33%, 0.09% free formaldehyde, and the degree of crystallinity was 10.92%. Tannin extract has a specific character on the wave number corresponding to the characteristics possessed by the imported tannin acacia standard. The presence of new functional groups and an increase in absorbance intensity of uptake at several wave numbers through infrared spectroscopy analysis on TRF as well as compregnated oil palm trunk indicate the occurrence bonds attributted by ether and methylene bridges to TRF and chemical compound on oil palm trunk. Oil palm trunk after compregnation significantly increased its density by 104.61%, hardness became 6 fold, and decreased the thickness swell to 85.98%. The oil palm trunk after compregnation also increased in quality from a wood strength class V to a wood strength class III, then, its potential for manufacturing exterior products.